Building up Autonomy Through Reading Strategies - Alexander Izquierdo Castillo; Sonia Jiménez Bonilla (Universidad Nacional de Colombia, 2014)
This article reports on an action research project conducted with six ninth grade students in a rural public school in Colombia. The purpose of the study was to determine how the implementation of three reading strategies (skimming, scanning, and making predictions), when reading topics selected by learners, helps them to improve their reading comprehension and promotes their autonomy in the learning process. The results show that these learners developed some autonomous features such as making decisions for learning and doing assigned homework, increasing reading awareness and motivation. Additionally, the training on reading strategies allowed them to succeed in their reading comprehension. We conclude that these reading strategies are tools that take learners along the path of autonomy.